American Social And Political Thought : A Reader - HESS, Andreas (Edit) (New York Univ. Press, 2002)
This reader provides substantial extracts from the core texts in the field of American social and political thought. It demonstrates the rich intellectual tradition of the United States, giving an unparalleled understanding of American society and politics through the reproduction of key writings from a wide variety of thinkers.